Permukiman Kawasan Danau Masa Lalu Di Jawa Timur - Gunadi Kasnowihadjo (Berkala Arkeologi Sangkhakala, 2015)
Archaeology without its public is nothing, it is a disturbing expression for archaeologists, which encourages them to make a policy that every archaeological research benefited the general public. Academically this study is hoped to find settlement patterns in the past around lakes. Furthermore, the study also tries to find models of the local wisdom of their communities. Values in local wisdom are very important for today’s communities and future generations. Considering the aim of the research, the method used is descriptive explorative with an inductive approach, while data collecting is done by carrying out excavations and surveys. It is hoped that the researchers can reveal how people lived in lake areas in the past. The condition of lake areas in the past both its communities and surrounding environment is the dream of future generations. This is the essence of studying archaeology because archaeology studies life in the past to be actualized and implemented in today’s life for the sake of the future generations.